Development of Reinforcement Grout Materials Based on Blast Furnace Slag according to the Content of Reinforcement Fiber. (19th October 2021) - Seo, H.; Kim, D. H.
Abstract : The grouting is used to reinforce soft ground and to prevent the leakage of water in the soil. The objective of the study is to enhance the compressive strength of grout materials by using reinforcing fibers and to increase the strength of soil using blast furnace slag powder. For this purpose, cement was replaced with the blast furnace slag powder by 30 to 60%. Furthermore, for comparison of carbon fibers with aramid fibers, each fiber was added by 0, 0.5, and 1.0% of the weight of material. As the contents of carbon fibers and aramid fibers increased, the uniaxial compressive strength increased. This is due to the interlocking of fibers in the grout material that increased the uniaxial compressive strength. Moreover, the grout material reinforced with aramid fibers showed an increase of uniaxial compressive strength by at least 20% compared to the carbon fibers. An environmental assessment was done through a heavy metal leaching test and a pH test. The test result reveals that about 50% of chromium (VI) leaching decreased as 30% more blast furnace slag powder was used but the pH test shows about 0.5 pH increased as 30% more blast furnace slag powder was used. Further study is necessary for the pH test.